The obstacles to the application of quality assurance in primary schools at the center of Babylon Governorate from the point of view of school principals and their assistants - Awad, Omar Falah (Al-Adab Journal, 2022)
The research aimed to identify the obstacles to the application of quality assurance in primary schools in the center of Babil Governorate from the point of view of school principals and their assistants. The scale was then distributed by the researcher to a group of school principals and their assistants, and according to their responses, the results were extracted.